Antibiotic Resistance of E. coli Isolated From a Constructed Wetland Dominated by a Crow Roost, With Emphasis on ESBL and AmpC Containing E. coli - Sen, Keya; Berglund, Tanner; Soares, Marilia A.; Taheri, Babak; Ma, Yizheng; Khalil, Laura; Fridge, Megan; Lu, Jingrang; Turner, Robert J. (Frontiers in Microbiology, 2019)
Information on the dissemination of antibiotic resistance mechanisms in the environment as well as wild life is needed in North America. A constructed wetland (where ~15,000 American crows roost) was sampled on the University of Washington Bothell Campus for the presence of antibiotic resistant E. coli (ARE). Crow droppings from individual birds and grab samples of water were collected in 2014-2015. E. coli were isolated by selective agar plating. The most frequent antibiotic resistance (AR) of the fecal isolates was to ampicillin (AMP) (53%), followed by amoxicillin-clavulanic acid (AMC) (45%), streptomycin (S) (40%) and nalidixic acid (NA) (33%). Water isolates had similar AR pattern and ~ 40% were multidrug resistant. Isolates from water samples collected during storm events showed higher resistance than isolates from no rain days to tetracycline, Amp, AMC, NA and gentamycin. Extended spectrum beta lactamase (ESBL) containing E. coli with the blactx-M was found in 3 water and 7 feces isolates while blacmy-2 in 19 water and 16 fecal isolates. Multilocus Sequence Typing analysis (MLST) yielded 13 and 12 different sequence types (STs) amongst fecal and water isolates, many of which could be correlated to livestock, bird, and humans. MLST identified ESBL E. coli belonging to the clinically relevant ST131 clone in 6 fecal and 1 water isolate. Three STs found in feces could be found in water on the same dates of collection but not subsequently. Thus, the strains do not appear to survive for long in the wetland. Phylogenetic analysis revealed similar distribution of the water and fecal isolates among the different phylo-groups, with the majority belonging to the commensal B1 phylo-group, followed by the pathogenic B2 phylo-group. This study demonstrates that corvids can be reservoirs and vectors of ARE and pathogenic E. coli, posing a significant environmental threat.